A Rare Presentation of Axial Chordoma and the Approach to Management - Muneer, Mohammed (Am J Case Rep, 2019)
Patient: Female, 50 Final Diagnosis: Axial chordoma Symptoms: Back ache • numbness • urine incontinence • weaknes of lower limbs Medication: — Clinical Procedure: — Specialty: Plastic Surgery OBJECTIVE: Rare disease BACKGROUND: Chordoma is a primary bone tumor that most commonly arises in the sacrococcygeal vertebrae and the spheno-occipital areas. Chordoma is a malignant tumor that should be distinguished from benign notochordal cell tumor (BNCT) of the spine. This report is of a rare case of axial chordoma and describes the challenging approach to diagnosis and management. CASE REPORT: A 50-year-old woman presented with a one-year history of a slowly growing swelling in the sacral region. She complained of numbness and progressive weakness in both lower limbs, and urinary incontinence. Computed tomography (CT) imaging showed a large destructive lesion involving the sacrum and coccyx with cranial extension to level S2 and invasion of the right and left S2–S3 neural foramina, sacral nerves, left gluteus maximums muscle, and adjacent subcutaneous tissue. The management approach included the early involvement of a multidisciplinary clinical team. En bloc resection of the tumor through an anterior and posterior approach was performed, and the defect was reconstructed later using bilateral rotational gluteal fascial flaps. CONCLUSIONS: Axial chordoma is a very rare, locally aggressive, and highly recurrent primary tumor of bone. The clinical management is challenging and requires early involvement of a multidisciplinary team. Following surgical resection, careful selection from limited available reconstructive surgical options is necessary to ensure that the surgical defect is repaired.